P97 Implementation of a regional trainee-led leadership and management programme for rheumatology trainees. (20th April 2020) - Benson, Rosalind; Sharp, Charlotte; Macphie, Elizabeth
Abstract: Background: We identified a lack of formal learning opportunities provided by Health Education England North West (HEE (NW)) to achieve the many leadership and management requirements stipulated by the Joint Royal College of Physicians' Training Board Speciality Training (ST) rheumatology curriculum. This gap was highlighted through discussion at the HEE (NW) Specialty Training Committee by trainee representatives and regional Training Programme Directors (TPD), in 2017. Furthermore, the merger of two pre-existing Deaneries (Mersey and NW) into the NW Local Education and Training Board (LETB) created a pressing need to develop a network across the region. Methods: Two regional ST representatives engaged with trainees across the new LETB through formal surveys and informal conversations regarding training to address this. Specialty trainees (STRs) elected a bi-annual half-day session in conjunction with an existing clinical regional event, the North West Rheumatology Club (NWRC). Sessions have covered a range of topics (Table 1) and provide an opportunity for networking across the deaneries. Learning objectives are mapped against ST curriculum. HEE (NW) TPDs support the programme, facilitating study leave. Meeting costs are supported by the NWRC. Trainees shape future sessions submitting topic ideas and have autonomy over content and speakers. Formal anonymous sessional feedback uses a Likert scale evaluating whether learning objectives have been met and quality of session delivery. Now entering its third year the scheme is well-established, with succession planning in place. Results: With feedback response rates of 85% (mean across 4 sessions), median scores are 5 (IQR 4.9-5) for meeting learning objectives and 5 (IQR 5-5) for session delivery. Free text feedback is overwhelmingly positive. Six months after sessions trainees reported 'feeling more encouraged to raise concerns', 'being more proactive in whistleblowing', 'having a better understanding of conflict situations', and 'better awareness of reasons for difference in individual behaviours'. Conclusion: Filling unmet training needs in leadership and management through trainee-led sessions provides an excellent learning opportunity for STRs both attending and leading the events, and facilitates cross-regional collaboration. This programme demonstrates the role of stakeholders to inform programme design successfully, showing excellent long-term impact in an important and previously underserved curriculum requirement. Disclosures: R. Benson None. C. Sharp None. E. Macphie Grants/research support; EM is the Secretary of the North West Rheumatology Club; meetings are supported by an unrestricted educational grant from UCB.